Kinerja Guru dalam Mewujudkan PAUD Berkualitas di TPA Hidayatus Shibiyan Kecamatan Pangean Kabupaten Kuantan Singingi - Yerita Yerita; Swandra Rahayu; Nopa Wilyanita (MASALIQ, 2026)
Early Childhood Education (ECE) constitutes an important foundation in shaping children’s cognitive, social, emotional, and moral development, so the quality of its services is largely determined by teacher performance as the main implementer of the learning process. However, in practice, the optimization of teacher performance still faces various constraints, such as discipline, creativity in the use of learning media, flexibility in curriculum implementation, and parental involvement in supporting children’s educational process. These conditions were also found at TPA Hidayatus Shibiyan, Pangean Subdistrict, Kuantan Singingi Regency. This study aims to describe and analyze teacher performance in realizing quality ECE at the institution and to identify the supporting and inhibiting factors in its implementation. This study employed a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The results showed that teacher performance was in the fairly good category, as reflected in the commitment to preparing lesson plans and implementing activities in accordance with the curriculum. Nevertheless, several aspects were still not optimal, especially the consistency of time management, the variety and creativity of learning media, the flexibility of curriculum implementation oriented toward children’s individual needs, and the partnership system with parents, which had not yet been structured. Thus, improving the quality of ECE requires strengthening supervision, continuous training, and the development of systematic partnership programs between the institution and families. These findings emphasize that the continuous improvement of teacher performance is an important prerequisite for realizing higher-quality ECE services.